The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s10164-018-0582-8
|View full text |Cite|
|
Sign up to set email alerts
|

Alarm call modification by prairie dogs in the presence of juveniles

Abstract: While several drivers of wildlife alarm calls have been identified, recent work on the impact of the audience in the plasticity of alarm calling indicates that intraspecific communication can drive the behavior. We build on this literature by assessing changes in call characteristics in black-tailed prairie dogs (Cynomys ludovicianus) in the presence of recently emerged juveniles. Alarm calls were elicited by approaching individuals, and then recorded using a shotgun microphone. Presence and distance of pups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This is a valid comparison because human non-verbal vocalizations, such as crying, laughing, grunting, groaning, moaning, or shrieking, do not have lexical content, are generated by subcortical limbic mechanisms, and are evolutionary counterparts of other mammalian vocalizations (for classification of human verbal and non-verbal vocalizations as well as pathological vocalizations, see [ 10 ]). Although animal vocalizations have many subtypes and may convey referential information or be situation-specific (e.g., in species of prairie dogs [ 11 , 12 , 13 ]), they do not represent language in a human sense and do not have grammatical structure, sentences, words, syllables, or even fully translatable meaning. Naming mammalian vocalizations as syllables, particularly those emitted in series, is a misnomer and mistake that is still repeated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This is a valid comparison because human non-verbal vocalizations, such as crying, laughing, grunting, groaning, moaning, or shrieking, do not have lexical content, are generated by subcortical limbic mechanisms, and are evolutionary counterparts of other mammalian vocalizations (for classification of human verbal and non-verbal vocalizations as well as pathological vocalizations, see [ 10 ]). Although animal vocalizations have many subtypes and may convey referential information or be situation-specific (e.g., in species of prairie dogs [ 11 , 12 , 13 ]), they do not represent language in a human sense and do not have grammatical structure, sentences, words, syllables, or even fully translatable meaning. Naming mammalian vocalizations as syllables, particularly those emitted in series, is a misnomer and mistake that is still repeated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially pertinent given that the function of the alarm call is to both warn conspecifics of approaching danger and to communicate to the predator that they have been detected (Isbell and Bidner 2016). Additional experiments conducted by our research group demonstrated that prairie dogs adjusted their alarm calls -reducing the central concentration of energy -when calling in the presence of vulnerable pups (Wilson-Henjum et al 2019). Adjustment in prairie dog communication, therefore, appears to be structured by social context mediated by spatial proximity to an approaching threat.…”
Section: Discussionmentioning
confidence: 94%
“…This provides evidence that the seemingly costly behaviour of an individual alerting a predator to their presence may have indirect fitness benefits (Shelley and Blumstein 2005). Moreover, we recently demonstrated that the presence of young influenced the alarm call characteristics of adult prairie dogswhereby they lowered the central concentration of energy in their calls (Wilson-Henjum et al 2019). The social context and function of alarm call production provides an interesting avenue for exploring the effects of exposure to anthropogenic noise on animal vocalisation, particularly when contrasted with findings from the significant body of work focussing on advertisement calls and songs (reviewed by Shannon, McKenna, et al 2016).…”
Section: Introductionmentioning
confidence: 88%
“…The development of this messaging system becomes intricate with human language. Whether the degree of development of the young at birth (which could relate to cognitive development; Scheiber et al 2017;Wilson-Henjum et al 2019) influences the complexity of vocalizations and other displays are yet to be determined.…”
Section: The Origins Of Substrate-borne Vibrational and Acoustic Comm...mentioning
confidence: 99%